Wintering yearling steers on dry bluestem pasture - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
The primary purpose of this test is to determine if yearling steers can be satisfactorily wintered on dry bluestem pasture. Different protein supplements as well as methods of feeding them on dry bluestem pasture are being tested.
Keywords: Beef; Steers; Dry bluestem pasture; Gain